Diagnostic Value of Isolated Mentalis Versus Mentalis Plus Upper Limb Electromyography in Idiopathic REM Sleep Behavior Disorder Patients Eventually Developing a Neurodegenerative Syndrome - Fernández-Arcos, Ana; Iranzo, Alex; Serradell, Mónica; Gaig, Carles; Guaita, Marc; Salamero, Manel; Santamaria, Joan (Sleep (New York, N.Y.), 2017)
Abstract Study Objectives: To compare two electromyographic (EMG) montages, isolated mentalis muscle versus mentalis in combination with upper limb muscles in the baseline diagnostic video-polysomnography (V-PSG) of patients with idiopathic REM sleep behaviors disorder (IRBD) who eventually were diagnosed with a clinically defined neurodegenerative syndrome. Methods: Forty-nine patients were included. At baseline, diagnosis of RBD was based on a typical history of dream enactment behaviors plus V-PSG showing REM sleep with qualitative increased EMG activity and/or abnormal behaviors. Quantification of EMG activity (tonic, phasic and “any”) in the mentalis and upper limb muscles (biceps brachii-BB, n = 36 or flexor digitorum superficialis-FDS, n = 13) was performed manually and compared with published cut-offs. Results: Nine (18.4%) patients had either tonic or phasic EMG below the cut-offs for the isolated mentalis and four of them (11.1 %) also had values below the cut-off for the mentalis combined with BB. All 13 patients recorded with the FDS were above the mentalis combined with FDS cut-off. For the diagnosis of IRBD, sensitivity of isolated mentalis was 81.6% and of the combination of mentalis plus upper limb muscles was 91.8% (p = .03). Audiovisual analysis showed abnormal REM sleep behaviors in all nine patients with values below the cut-offs. Conclusion: Quantification of EMG activity in the upper limbs combined with the mentalis increases the ability to diagnose IRBD when compared with the isolated measurement of the mentalis. Detection of typical abnormal behaviors during REM sleep with audiovisual analysis is essential for the diagnosis of IRBD in patients with EMG values below the published cut-offs.